Integrating Artificial Intelligence in Hijri Month Determinatiton: a Maqasid Approach - Vivit Fitriyanti (Faculty of Law, Mulawarman University, 2025)
Determining the beginning of the Hijri month, which is the basis of the Islamic calendar, plays an important role in carrying out Muslim worship, such as Ramadan, Eid al-Fitr, and Eid al-Adha. Traditional methods based on rukyat often experience obstacles due to weather factors and geographical differences, so astronomical technology has begun to be used to provide higher accuracy and consistency. This study aims to evaluate the use of astronomical technology in determining the beginning of the Hijri month reviewed from the perspective of Maqashid Syariah. The Maqashid Syariah approach, which includes protection of religion, soul, mind, descendants, and property, is used as an analytical framework to assess the impact of technology in creating welfare for the people. This study uses a qualitative approach with literature analysis and case study methods. A qualitative approach to understand how technology can be integrated into the process of determining the Hijri calendar and how this can be seen through the principles of Maqashid Syariah. The literature study aims to identify technologies that have the potential to be applied in determining the crescent moon . The results of the study indicate that astronomical technology has great potential in improving the accuracy, efficiency, and timeliness in determining the beginning of the Hijri month. Digital telescopes and remote sensing overcome the limitations of manual crescent observations, while simulation software and AI provide long-term predictions that help the consistency of the Hijri calendar. This technology supports Maqashid Syariah by strengthening the unity of worship, providing rational scientific data, and reducing social conflict due to differences in calendars. However, this study found that there were obstacles to implementation, such as differences in school of thought and limited infrastructure in some areas. Thus, the adoption of astronomical technology in determining the Hijri calendar can create wider benefits for Muslims if these challenges can be overcome through global consensus and increased access to technology.